(De)Constructing the Iron wall: the story of Palestinian military infiltration from the Gaza Strip - Yara Nassar (23124679) (2025)
This article examines the evolution of Palestinian infiltration tactics in response to Israel’s security barriers, culminating in Hamas’s 7 October attack. It introduces the Security Barrier-Adaptation Model (SBAM) to analyse the cyclical interplay between Israeli fortifications and Palestinian countermeasures, identifying three core phases: barrier innovation, counter-adaptive tactics, and systemic readjustment. It highlights how Palestinian armed groups have innovated tactics, using tunnels, land, and sea routes, to infiltrate and circumvent Israeli defenses. By contextualizing infiltration within asymmetric warfare dynamics, the article reveals the limitations of static defense strategies and the iterative adaptation of adversarial strategies. Other Information Published in: Small Wars & Insurgencies License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1080/09592318.2025.2474526